Development of 2′-O-Methyl and LNA Antisense Oligonucleotides for SMN2 Splicing Correction in SMA Cells - Marianna Maretina; Arina Il’ina; Anna Egorova; Andrey Glotov; Anton Kiselev (Biomedicines, 2023)
Spinal muscular atrophy (SMA) is a devastating neurodegenerative disease caused by mutations in the SMN1 gene. Existing therapies demonstrate positive results on SMA patients but still might be ameliorated in efficacy and price. In the presented study we designed antisense oligonucleotides (AONs), targeting intronic splicing silencer sites, some were modified with 2′-O-methyl, others with LNA. The AONs have been extensively tested in different concentrations, both individually and combined, in order to effectively target the ISS-N1 and A+100G splicing silencer regions in intron 7 of the SMN2 gene. By treating SMA-cultured fibroblasts with certain AONs, we discovered a remarkable increase in the levels of full-length SMN transcripts and the number of nuclear gems. This increase was observed to be dose-dependent and reached levels comparable to those found in healthy cells. When added to cells together, most of the tested molecules showed a remarkable synergistic effect in correcting splicing. Through our research, we have discovered that the impact of oligonucleotides is greatly influenced by their length, sequence, and pattern of modification.